A Survey of Indonesian Islamic Senior High School Teachers’ Vocabulary Teaching Strategies /Activities - Putri, Fauzana; Wulyani, Anik Nunuk; Tresnadewi, Sintha (Universitas Lancang Kuning, 2023)
The current study is designed to investigate vocabulary teaching strategies/activities employed by teachers in Islamic senior high schools by referring to the principle of the Four Strands proposed by Nation (2007). A survey research design was used in line with the study's goal. English teachers who teach in Islamic senior high schools or Madrasah Aliyah, both public and private schools in West Sumatera, were the study's target demographic. The questionnaire and interviews collected the information required to respond to the survey's question. The finding reveals that teachers employ four kinds of strategies/activities following the Four Strands by Nation (2007) in teaching vocabulary to students. The findings of the study suggest that this study might give an insight that more strategies/activities need to be done by teachers to enhance vocabulary learning. The findings of the study provide some implications for future practice in teaching-learning process of teaching vocabulary. In reference to the findings, the recommendations are addressed to EFL teachers and future researchers. Some implications of the study are also discussed.